Histological Changes In The Intestine, Muscle Of Brotia Costula (Gastropoda: Pachychilidae) Exposed Along The Langat River - Awadelseed, Abdelgalil Osman (2002)
Histological changes in the intestine, gills and feet of Brotia costula exposed to six stations along the Langat River were studied. Three other parameters such as susceptibility of the snail to river's water that was expressed in rLT 50 (relative Lethal Time 50%), water quality of the river and normal ultrastructure of the snail's alimentary canal were also studied. Snails collected from the clean upper part of Langat River in Selangor were transferred to six stations along the same river. The stations selected were either situated in the areas of agriculture, villages, town or industries. Thirty snail, kept in cages, were left submerged at each station for about four months (from March to July 2000) and sampled weekly for the examination of the histological changes in their intestines, gills and feet. Results from the light microscopic examinations revealed that erosion and necrosis of intestinal epithelial cells were common in snails exposed to all stations. Hypertrophy and formation of spaces in between epithelial cells were only developed